Case Report: Use of Subcutaneous Midazolam During an Episode of Catatonia - Raymond, Valentin; Véry, Etienne; Jullien, Adeline; Eyvrard, Fréderic; Anguill, Loic; Yrondi, Antoine (Frontiers in Psychiatry, 2021)
Midazolam is a benzodiazepine (BZD) mainly used in anaesthetic induction due to its pharmacokinetic features. Its place in the therapeutic management of catatonia remains to be determined. Here we present the case of a 65-year-old man who presented with a first episode of catatonia with opposition to any form of oral treatment, where a single dose of 1 mg of subcutaneous (SC) Midazolam permitted clinical improvement allowing oral treatment to be given. The patient’s history notably included a renal transplant linked to Polycystic Kidney Disease (PKD) and no history of psychiatric illness nor of any use of psychotropic drugs. As the patient refused to drink or eat and ceased answering basic questions, a psychiatric assessment was required. A diagnosis of Catatonic disorder due to a general medical condition (DSM 5 - 293.89/ ICD10 [F06.1]) was made. A Bush-Francis Catatonia Rating Scale (BFCRS) analysis returned a score of 15 out of 62, with stupor, mutism, negativism, staring, withdrawal, rigidity, and stereotypy. As the negativism prevented the patient from taking any form of oral treatment, after a brief discussion with the unit’s physician, it was decided to administer 1 mg of SC Midazolam. One hour later, the patient was more responsive and compliant, and agreed to drink, eat, and take medication. Thus, the catatonic signs of mutism, negativism, staring, and withdrawal were resolved, but waxy flexibility and catalepsy appeared, leading to a new BFCRS score of 10 out of 62. Oral treatment with 2.5 mg Lorazepam, 4 times a day, was then initiated. Midazolam could be a safer choice compared with the other options available, such as other SC BZD, considering the complex safety profile of this patient with renal insufficiency. This situation represents the first report of using SC Midazolam as an injectable treatment for catatonia. More studies are needed to assess the clinical pertinence of SC Midazolam in the treatment of catatonia.